2007
DOI: 10.2214/ajr.07.2186
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Cement Distribution Pattern and New Compression Fracture After Percutaneous Vertebroplasty

Abstract: Although cement distribution patterns do not significantly affect initial clinical response, a higher incidence of new compression fractures is seen in patients with treated vertebrae exhibiting a cleft pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 9 publications
1
52
0
2
Order By: Relevance
“…Treatment of multiple vertebrae at initial presentation and compression fractures at the T-L junction may stimulate untreated vertebrae biomechanically, which was not proven in our study [7,9,11]. The distribution pattern of the cement may relate to cement amount and height restoration, and can affect the tension on the adjacent vertebrae [22]. This effect was not observed even though cement volume was significantly higher in compact type (P \ 0.01).…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Treatment of multiple vertebrae at initial presentation and compression fractures at the T-L junction may stimulate untreated vertebrae biomechanically, which was not proven in our study [7,9,11]. The distribution pattern of the cement may relate to cement amount and height restoration, and can affect the tension on the adjacent vertebrae [22]. This effect was not observed even though cement volume was significantly higher in compact type (P \ 0.01).…”
Section: Discussionmentioning
confidence: 57%
“…Cement distribution was classified as follows: (1) compact type-vertebrae with compact and solid filling, and (2) trabecular type-vertebrae with sponge-like filling [22] ( Fig. 2).…”
Section: Review Of Patient Datamentioning
confidence: 99%
See 1 more Smart Citation
“…To reduce the risk, many researchers have attempted to identify factors that affect the dosage or pattern of cement. For instance, Tanigawa et al (8) classified patterns of bone cement distribution based on post-procedure fluoroscopy for cleft patterns, compact and solid cement filling patterns in vertebrae, and trabecular or sponge-like filling patterns. They concluded that the volume of cement injected was greater for compact and solid cement filling patterns than for trabecular or sponge-like filling patterns, and the incidence of new compression fractures was higher for compact and solid cement filling pattern groups.…”
Section: Discussionmentioning
confidence: 99%
“…Literatür incelendiğinde PVP işlemine bağlı enfeksiyon, epidural kanama, yağ embolisi, kardiak hasar gibi ciddi ek komplikasyonlar bildirilmiş olsada oldukça nadirdirler ve bizim klinik tecrubemizinde bu yönde olduğu izlenmiştir.Bunun yanında kullanılan kemik çimento akışkanlığı konusunda belirleyici bir ölçüm yönteminin bulunmayışı ile önerilen dişmacunu kıvamını elde etme konusunda gerekli koşulların sağlanması için standardın yerleşmemiş olması da etkileyici yöntemlerden biridir. Eğer yoğun kıvam elde edilirse işlemi yapmanın zorlaştığı ancak kaçak olasılığının azaldığı , yoğunluğun azalması ile birlikte kaçak riskinin arttığı da bilinmelidir (35)(36)(37). Optimum koşulları sağlamanın cerrahın deneyimi ile doğru orantılı olduğu düşünülmektedir.…”
Section: Gereç Ve Yöntemunclassified